Progress of the Catalytic Deactivation of H-ZSM-5 Zeolite in Glycerol Dehydration - Catuzo, Gabriel L. [UNESP]; Possato, Luiz G. [UNESP]; Sad, María Eugenia; Padró, Cristina; Martins, Leandro [UNESP] (Wiley, 2021)
Glycerol conversion into value-added chemicals has received much attention due to the prospect of increasing the biodiesel industry‘s profitability. The dehydration of glycerol is one of the most explored reactions in the valorization of glycerol, and the zeolite H-ZSM-5 is one of the furthermost used structures. In this study, several characterization techniques were used to investigate the detailed aging of coke in spent H-ZSM-5 zeolites after their use in the gas-phase glycerol dehydration to produce acrolein. The carbonaceous deposits formed almost totally in the first minutes of the reaction. They rapidly got trapped inside the pores, hampering the accessibility to active sites and the zeolite‘s full catalytic action. Two types of coke were formed during the reaction: polyglycols, on the external surface, and aromatics, inside the pores, representing the majority (∼98 wt.%) of the carbonaceous compounds. Besides, aromatic compounds age over time, becoming bulkier and more deficient in hydrogen. We also found a correlation between the amount of coke, its size, accessibility to the acid active sites, and changes in crystallographic parameters of the zeolite with the presence of coke.
Keywords: Acid catalysis; Coke; Deactivation; Dehydration; Glycerol; ZSM-5 zeolite